The association between miR-499 polymorphism and cancer susceptibility: a meta-analysis - Xu, Zhongfei (Onco Targets Ther, 2015)
BACKGROUND: MicroRNAs are a class of new noncoding RNA that play important roles in the pathogenesis of tumor. Rs3746444 in miR-499 is suggested to be associated with cancer susceptibility. In the present study, we assess the association between miR-499 rs3746444 polymorphism and cancer susceptibility through a meta-analysis. METHODS: We searched relevant articles from the PubMed and Embase databases. We screened all the resulting articles for adherence to the inclusion and exclusion criteria. The associations between miR-499 polymorphism and cancer susceptibility were estimated by computing the odds ratios (ORs) and 95% confidence intervals (CIs). All analyses were performed using Stata software. RESULTS: There are 18 datasets included in the analysis. Statistically significant associations were found between the miR-499 rs3746444 polymorphism and susceptibility to cancer (GG versus AA: OR =1.24, 95% CI: 1.01–1.52; G versus A: OR =1.11, 95% CI: 1.01–1.23). A subsequent analysis, on the basis of ethnicity for the population characteristic, showed that Asians had increased susceptibility to cancer (GG versus AA: OR =1.32, 95% CI: 1.09–1.59; GG + AG versus AA: OR = 1.17, 95% CI: 1.01–1.37). In the subgroup analysis of tumor type, none of the genetic models had statistically significant results. The meta-regression suggested that race and cancer types are not the source of heterogeneity in the present meta-analysis. No publication bias was detected by either the inverted funnel plot or Egger’s test. CONCLUSION: Rs3746444 in miR-499 might be related to susceptibility to cancer.